Remarks at the Development Committee Virtual Meeting - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, summarized the challenging environment now facing the World Bank Group, as the unprecedented COVID-19 pandemic affects the world. He is expecting a major global recession to complicate the devastating health crisis. The extreme poor in IDA countries will be severely affected. He reviewed the measures taken by the World Bank Group in response to the emergency. The program has three pillars: protecting the poorest and most vulnerable households; supporting businesses and saving jobs; implementing emergency health operations in developing countries to strengthen economic resilience. To this end, USD 160 billion in financing over the next 15 months are available. He summarized the debt relief initiative championed at the G20 meeting. He recapped the activities during the Spring meetings and recent high-level appointments.